The mediating role of job stress on the relationship between job motivation and job satisfaction among emirati male teachers in Abu Dhabi - Salem, Almessabi Mohamed Ali Ahmed (Tanjong Malim, 2024)
The mediating role of job stress on the relationship between job motivation and job satisfaction among emirati male teachers in Abu Dhabi by Salem, Almessabi Mohamed Ali Ahmed